How and Why Does History Matter for Development Policy? - Woolcock, Michael (2012)
The consensus among scholars and policy-makers that 'institutions matter' for development has led inexorably to a conclusion that 'history matters', since institutions clearly form and evolve over time. Unfortunately, however, the next logical step has not yet been taken, which is to recognise that historians (and not only economic historians) might also have useful and distinctive insights to offer. This article endeavours to open and sustain a constructive dialogue between history--understood as both 'the past' and 'the discipline'--and development policy by (a) clarifying what the craft of historical scholarship entails, especially as it pertains to understanding causal mechanisms, contexts, and complex processes of institutional change; (b) providing examples of historical research that support, qualify, or challenge the most influential research (by economists and economic historians) in contemporary development policy; and (c) offering some general principles and specific implications that historians, on the basis of the distinctive content and method of their research, bring to development policy debates.